Diversity of Community College Trustees: Expanding Opportunities - Terry A. Calaway; Carl B. Smalls (Educational Considerations, 2025)
The goal of the study was to explore how a diverse community college board might effectively influence the college mission by focusing on the greater impact of diversity, equity, inclusion, and belonging as well as the environment that may result from these policy discussions. The researchers explored if and how the establishment of diverse boards of trustee candidates can influence the number of African American faculty, administrators, and senior leaders who join their colleges, with the eventual goal of influencing student success itself when the environment is determined to be equitable to student and community demographics.
Keywords: Trustees; DEI; Community Colleges; Community College Boards; African American